Factors associated with running out of food in the households during COVID-19 in Indonesia: Analysis RGA UN Women data 2021 - Adi Yeremia Mamahit; Agnescia Clarissa Sera; Lili Amaliah; Maretalinia Maretalinia; Tommi Prayitno (Postgraduate, University of Mataram, 2023)
The issue of food insecurity during COVID-19 has occurred around the world, including in Indonesia. This study focused on factors associated with running out of food in the households as the outcome. The objective of this study was to examine the variables associated with running out of foods during the COVID-19 pandemic in Indonesia. This study used secondary data RGA from UN Women website to explore univariate, bivariate, and multivariate analysis. The results revealed that the main factors influencing running out of foods are five variables such as worries would not having enough food to eat, being unable to eat healthy and nutritious food, eating only a few kinds of foods, eating less than enough, and being hungry but did not eat. There are two variables that revealed moderate correlation such as skipping a meal and going without eating for a whole day. The strongest variable is HHâ€™s head reported were hungry but did not eat which were 5.48 times more likely to run out of foods during the pandemic. Intervention and collaboration with other stakeholders need to be arranged well to prevent the severity food insecurity. Â